2021
DOI: 10.1101/2021.09.09.459688
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evaluating the power and limitations of genome-wide association mapping in C. elegans

Abstract: A central goal of evolutionary genetics in Caenorhabditis elegans is to understand the genetic basis of traits that contribute to adaptation and fitness. Genome-wide association (GWA) mappings scan the genome for individual genetic variants that are significantly correlated with phenotypic variation in a population, or quantitative trait loci (QTL). GWA mappings are a popular choice for quantitative genetic analyses because the QTL that are discovered segregate in natural populations. Despite numerous successf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2

Relationship

6
0

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 65 publications
0
10
0
Order By: Relevance
“…We considered Bayes Factors (BFs) above 20 as evidence of a significant genotype-environment association. We also performed GEA with the NemaScan pipeline, a GWA tool specifically designed for C. elegans, which is available at https://github.com/AndersenLab/NemaScan (Widmayer, Evans, Zdraljevic, & Andersen, 2021).…”
Section: Genotype-environment Association and Local Adaptationmentioning
confidence: 99%
See 1 more Smart Citation
“…We considered Bayes Factors (BFs) above 20 as evidence of a significant genotype-environment association. We also performed GEA with the NemaScan pipeline, a GWA tool specifically designed for C. elegans, which is available at https://github.com/AndersenLab/NemaScan (Widmayer, Evans, Zdraljevic, & Andersen, 2021).…”
Section: Genotype-environment Association and Local Adaptationmentioning
confidence: 99%
“…However, methods to make GEA more robust to various types of structure exist. In the case of a GEA using GWA, the NemaScan pipeline accounts for the relatedness and genetic structure among strains with a genomic relationship matrix that can at least partially account for population structure (Widmayer et al, 2021;Yang et al, 2011). On the other hand, BayPass uses Bayesian hierarchical models to explicitly account for the scaled covariance matrix of population allele frequencies (Gautier, 2015).…”
Section: The Genomic Architecture Of Local Adaptationmentioning
confidence: 99%
“…We also explored associations with latitude and longitude because selective pressures associated with geographic location could also underlie signatures of local adaptation. Using the NemaScan GWA pipeline (Widmayer et al, 2021 ), we found 39 regions of the genome that were associated with environmental or geographic parameters (Figure 7 ). The BayPass genome‐wide scan revealed 108 regions of the genome that were associated with environmental or geographic parameters (Figure 7 ).…”
Section: Resultsmentioning
confidence: 99%
“…However, methods to make GEA more robust to various types of structure exist. In the case of a GEA using GWA, the NemaScan pipeline accounts for the relatedness and genetic structure among strains with a genomic relationship matrix (Widmayer et al, 2021 ; Yang et al, 2011 ). On the other hand, BayPass uses Bayesian hierarchical models to explicitly account for the scaled covariance matrix of population allele frequencies (Gautier, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation